Stanislavski's objectives, given circumstances and magic "if"s through the lens of optimal experience. Issue 2 (2nd July 2016) - Polanco, Fabio; Bonfiglio, Diane B. V.
Abstract: Actors may recall a feeling of exhilaration during periods of inspired acting; they felt at one with the material, their partners, and the audience. Such a state is referred to in the psychological literature as flow. Mihalyi Csikszentmihalyi proposes that flow is a state of highly ordered consciousness in which all psychic energy is focused on the task at hand. Csikszentmihalyi describes elements of flow as including such aspects as a high degree of concentration, focused attention and the pursuit of clear goals. Actors study methodologies in order to purposely place themselves in this state as opposed to it being a happy accident. It is possible that achievement of the flow state may be facilitated by certain techniques that are contained within Konstantin Stanislavski's system, and that the enhanced performance quality that results from the practice of those techniques actually represents the achievement of flow. In particular, Stanislavski's focus on objectives, given circumstances, and magic "if"s may be related to the experience of flow. This paper explores links between Stanislavski's system and Csikszentmihalyi's work on flow.